Comparison of Hemodynamic Brain Responses Between Big Wave Surfers and Non-big Wave Surfers During Affective Image Presentation - Showstark, Mary; Bahadursingh, Ryan; Zhang, Sheng; Fry, Adam; Kozminski, Barbara; Lundstam, Per; Putrino, David (Frontiers in Psychology, 2022)
Background: Many extreme sports athletes are exposed to high-risk environments when training and competing. Big wave surfers are one such group who are seemingly willing to tolerate a higher level of risk than non-big wave surfers. This study explored potential neurophysiological and psychometric differences between big and non-big wave surfers. Methods: Thirteen big wave surfers (BWS) and ten non-big wave surfers (CON) viewed a series of images from the International Affective Picture System (IAPS) while undergoing brain functional magnetic resonance imaging (fMRI). The Fear Schedule Survey-III, Arnett Inventory of Sensation Seeking, Discrete Emotions Questionnaire, and Positive and Negative Affect Schedule were also completed. Results: The BWS group demonstrated higher blood-oxygen level dependent (BOLD) signal change in the insula, visual cortex, and periaqueductal gray, whereas the CON group displayed increased hypothalamus activation in response to high amplitude negative valence (HAN) image presentation. Psychophysiological interaction (PPI) analyses found CON showed significant interactions between frontal and temporal cortical regions as well as between the hypothalamus and the insula, frontal, and temporal cortices during HAN image presentation that were not seen in BWS. No differences between groups were found in their responses to the questionnaires. Conclusions: Our findings demonstrate significant differences in brain activation between BWS and CON in response to the presentation of HAN IAPS images, despite no significant differences in scores on psychometric questionnaires.